Influence of Robusta Coffee (Coffeea Canephora) Waste Type and Coffee Waste Substitution on Chemical and Organoleptics of Roasted Brownies - Arzetha ragilia Novita; Fadjar Kurnia Hartati (Demeter: Journal of Farming and Agriculture, 2023)
Most Indonesians choose robusta as a coffee that is often consumed, one type of robusta that is often consumed is arjuna and temanggung. With the increase in coffee consumption, there will also be a lot of coffee grounds left. Coffee has a distinctive aroma coffee also has several contents which include several flavonoid compounds and other chemical compounds. So that coffee grounds can still be utilized, one of which is as a substitute for cocoa powder in baked brownies. The purpose of this study was to determine the type of robusta coffee grounds and the best coffee grounds substitution on chemistry and organoleptic. This study used a Completely Randomized Design (CRD) which was arranged with factorial and consisted of two factors, namely robusta arjuno coffee and robusta temanggung with each concentration of 15 g, 22.5 g, 30 g per treatment. The results showed that the type of interaction effect of robusta coffee grounds with coffee grounds substitution had no significant effect on moisture content, ash content and fiber content. Organoleptic test based on Kruskal Wallis showed that the addition of coffee grounds did not significantly affect the parameters of color, aroma, taste and tenderness. The best treatment for brownie products is 30 g robusta arjuno coffee grounds with treatment code (R1A3), with the highest Result Value (NH) of 0.577. And has a non-parametric criteria value of aroma 4.90 (neutral), fiber 9.08%, water 9.08%, tenderness 4.96 (neutral), ash 2.80%, taste 5.32 (somewhat like), color 5.29 (somewhat like).